Cross-Talk Between Tumor Cells Undergoing Epithelial to Mesenchymal Transition and Natural Killer Cells in Tumor Microenvironment in Colorectal Cancer - Vuletić, Ana; Mirjačić Martinović, Katarina; Tišma Miletić, Nevena; Zoidakis, Jerome; Castellvi-Bel, Sergi; Čavić, Milena (Frontiers in Cell and Developmental Biology, 2021)
Tumor cells undergoing epithelial to mesenchymal transition (EMT) and immune cells in tumor microenvironment (TME) reciprocally influence each other. Natural killer (NK) cells, the effector cells of the innate immune system, play a significant role in the control of metastasis in colorectal cancer (CRC). In this review we discuss modalities of cross-talk between tumor cells and NK cells, with regard of EMT-driven changes. Immune cells, by supplying TME with bioactive molecules including cytokines, chemokines, enzymes, metabolites, and by physical interactions with tumor cells, via their receptors, represent an important factor that affects EMT. Chronical inflammation in TME favorizes tumor growth and invasiveness. Cytokines in TME, e.g. TGF-β, the most potent EMT inducer, stimulate synthesis of EMT promoting transcription factors. Although, the cross-talk between immune cells and tumor cells in general favors the induction of EMT and inhibition of antitumor immune responses, there are some changes in the immunogenicity of tumor cells during EMT of CRC that increase their susceptibility to NK cell cytotoxic lysis. Aside from the loss of major histocompatibility (MHC) class I expression on tumor cells during EMT, EMT-associated changes in expression of ligands for NK cell receptors such as upregulation of NKG2D receptor ligands, upregulation of adhesion CADM1 molecule, and decrease in E-cadherin, render tumor cells more susceptible to NK cell attacks. However, suppressive TME also downmodulates the expression of activating NK cell receptors, induces shedding of activating NK cell ligands from tumor cells by proteolytic enzymes, which altogether negatively affects the overall NK cell function. Furthermore, EMT in CRC is often associated with increased expression of programed cell death ligand (PD-L1) and expression of immune checkpoint molecules PD-1, TIGIT and TIM3 on functionally exhausted NK cells in TME. In the settings of immunotherapy with checkpoint inhibitors, the reactivation of exhausted NK cells may contribute to clinical benefit.